Mind-Body Practices and the Self: Yoga and Meditation Do Not Quiet the Ego but Instead Boost Self-Enhancement. (August 2018) - Gebauer, Jochen E.; Nehrlich, Andreas D.; Stahlberg, Dagmar; Sedikides, Constantine; Hackenschmidt, Anke; Schick, Doreen; Stegmaier, Clara A.; Windfelder, Cara C.; Bruk, Anna; Mander, Johannes
Mind-body practices enjoy immense public and scientific interest. Yoga and meditation are highly popular. Purportedly, they foster well-being by curtailing self-enhancement bias. However, this "ego-quieting" effect contradicts an apparent psychological universal, the self-centrality principle. According to this principle, practicing any skill renders that skill self-central, and self-centrality breeds self-enhancement bias. We examined those opposing predictions in the first tests of mind-body practices' self-enhancement effects. In Experiment 1, we followed 93 yoga students over 15 weeks, assessing self-centrality and self-enhancement bias after yoga practice (yoga condition, n = 246) and without practice (control condition, n = 231). In Experiment 2, we followed 162 meditators over 4 weeks (meditation condition: n = 246; control condition: n = 245). Self-enhancement bias was higher in the yoga (Experiment 1) and meditation (Experiment 2) conditions, and those effects were mediated by greater self-centrality. Additionally, greater self-enhancement bias mediated mind-body practices' well-being benefits. Evidently, neither yoga nor meditation fully quiet the ego; to the contrary, they boost self-enhancement.